2019
DOI: 10.1136/annrheumdis-2018-214816
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with systemic sclerosis treated with rituximab in contemporary practice: a prospective cohort study

Abstract: ObjectiveTo assess the safety and efficacy of rituximab in systemic sclerosis (SSc) in clinical practice.MethodsWe performed a prospective study including patients with SSc from the European Scleroderma Trials and Research (EUSTAR) network treated with rituximab and matched with untreated patients with SSc. The main outcomes measures were adverse events, skin fibrosis improvement, lung fibrosis worsening and steroids use among propensity score-matched patients treated or not with rituximab.Results254 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
2
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(105 citation statements)
references
References 47 publications
(87 reference statements)
1
82
2
20
Order By: Relevance
“…Consistent with previous reports, Th2 cell numbers were greatly increased in bullous pemphigoid tissues and outnumbered those in SSc and healthy control skin ( Figure 2C and Supplemental Figure 2). Despite the 5-to 10-fold greater number of CD4 + T cells in skin biopsies of bullous pemphigoid patients compared with SSc biopsies, we found the absolute numbers of tissue-infiltrating T lymphocytes have not been systematically interrogated at the tissue level (22)(23)(24).…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Consistent with previous reports, Th2 cell numbers were greatly increased in bullous pemphigoid tissues and outnumbered those in SSc and healthy control skin ( Figure 2C and Supplemental Figure 2). Despite the 5-to 10-fold greater number of CD4 + T cells in skin biopsies of bullous pemphigoid patients compared with SSc biopsies, we found the absolute numbers of tissue-infiltrating T lymphocytes have not been systematically interrogated at the tissue level (22)(23)(24).…”
Section: Resultscontrasting
confidence: 57%
“…Although prominent numbers of both B and T cells were observed, the absolute number of infiltrating T cells was greater than those of infiltrating B cells ( Figure 1, A and B). Although randomized double-blind clinical trials examining the utility of B cell depletion therapy in SSc have not been performed, some studies have reported clinical improvement with rituximab, especially in the context of early diffuse SSc (22,23). Additionally, activated B cells have been observed in the circulation of SSc patients (24,36).…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, from our study, RTX has been shown to be a more effective drug than CYC for Japanese SSc patients. Whereas, there are some studies in which the change of pulmonary function and skin sclerosis by RTX treatment was not statistically significant . There are some factors that explain the good response to the treatment in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…Whereas, there are some studies in which the change of pulmonary function and skin sclerosis by RTX treatment was not statistically significant. 46,47 There are some factors that explain the good response to the treatment in our study. For example, difference in the duration of disease, the presence of anti-topo I antibodies, the levels of serum KL-6, and the severity of lung fibrosis might be related to this result.…”
Section: Discussionmentioning
confidence: 71%
“…A follow-up study of 254 patients in the EUSTAR database treated with rituximab, of whom 58% were treated for lung involvement, did not show effects on FVC or DLco. After a median follow-up of 2 years, compared to 9575 control patients matched for propensity score, rituximab-treated patients were more likely to have an improvement in skin fibrosis, but did not have significantly different rates of decline in FVC or DLco [69]. An ongoing multicenter randomized trial in the UK, RECITAL, is assessing the efficacy and safety of rituximab given intravenously at baseline and week 2 versus monthly intravenous CYC in 116 subjects with ILD associated with SSc, idiopathic inflammatory myositis, or mixed connective tissue disease [70].…”
Section: Rituximabmentioning
confidence: 99%